Perkembangan Destinasi Wisata Alam Tirta Alami Menjadi Daya Tarik Wisata di Kecamatan 2x11 Kayu Tanam Tahun 1994-2022 - Ayuni Nadia (PAMA Aksara, 2023)
This research examines the development of natural tirta natural tourist destinations into tourist attractions in the 2x11 year timber planting district (1994-2022). This study aims to explain the development of natural tourist destinations from 1994-2022 so that they can make it attractive for visitors who will travel there. This study uses the historical method using the following steps: data collection or heuristics, source criticism, interpretation, historiography. In obtaining primary or secondary data, the authors conducted it in two ways, namely library research and field studies. The results of this study indicate that the initial existence of the Tirta Alami baths was the land acquisition that occurred in 1994 and the management of the Tirta Alami baths began by PT Andalas Permai Internasional in 1996. Initially these baths had the same number of pools until now. The coolness and beauty of the Tirta Alami bath makes it an attraction for visitors to come to this tour. During the ownership of PT Andalas Permai Internasional in 1996-2018 the focus was on the management of the Tirta Alami baths. In 2018 there was a change in ownership to PT Dempo Anailand, Anailand did not only focus on natural tirta tourism but also on anai peak tourism. Many of the games in the natural tirta baths were moved to the Anai peak tour so that the visitors' interest was divided when they were in the area of PT Dempo Anailand which caused a decline at the start of the move.